Effects of degraded agent and munitions anomalies on chemical stockpile disposal operations (National Academies Press, 2004)
The U.S. Army is in the process of destroying its entire stock of chemical weapons. To help with stockpile disposal, the Army's Chemical Stockpile Disposal Program (CSDP), in 1987, asked the National Research Council (NRC) for scientific and technical advice. This report is one in a series of such prepared by the NRC over the last 16 years in response to that request. It presents an examination of the effect of leaking munitions (leakers) and other anomalies in the stored stockpile on the operation of the chemical agent disposal facilities. The report presents a discussion of potential causes of these anomalies, leaker tracking and analysis issues, risk implications of anomalies, and recommendations for monitoring and containing these anomalies during the remaining life of the stockpile.